Differential Aggregation and Phosphorylation of Alpha Synuclein in Membrane Compartments Associated With Parkinson Disease - Canerina-Amaro, Ana; Pereda, Daniel; Diaz, Mario; Rodriguez-Barreto, Deiene; Casañas-Sánchez, Verónica; Heffer, Marija; Garcia-Esparcia, Paula; Ferrer, Isidro; Puertas-Avendaño, Ricardo; Marin, Raquel (Frontiers in Neuroscience, 2019)
The aggregation of α-synuclein (α-syn) is a major factor behind the onset of Parkinson’s disease (PD). Sublocalization of this protein may be relevant for the formation of multimeric α-syn oligomeric configurations, insoluble aggregates that form Lewy bodies in PD brains. Processing of this protein aggregation is regulated by associations with distinct lipid classes. For instance, instability of lipid raft (LR) microdomains, membrane regions with a particular lipid composition, is an early event in the development of PD. However, the relevance of membrane microdomains in the regulation and trafficking of the distinct α-syn configurations associated with PD remains unexplored. In this study, using 6- and 14-month-old healthy and MPTP-treated animals as a model of PD, we have investigated the putative molecular alterations of raft membrane microstructures, and their impact on α-syn dynamics and conformation. A comparison of lipid analyses of LR microstructures and non-raft (NR) fractions showed alterations in gangliosides, cholesterol, polyunsaturated fatty acids (PUFA) and phospholipids in the midbrain and cortex of aged and MPTP-treated mice. In particular, the increase of PUFA and phosphatidylserine (PS) during aging correlated with α-syn multimeric formation in NR. In these aggregates, α-syn was phosphorylated in pSer129, the most abundant post-transductional modification of α-syn promoting toxic aggregation. Interestingly, similar variations in PUFA and PS content correlating with α-syn insoluble accumulation were also detected in membrane microstructures from the human cortex of incidental Parkinson Disease (iPD) and PD, as compared to healthy controls. Furthermore, structural changes in membrane lipid microenvironments may induce rearrangements in raft-interacting proteins involved in other neuropathologies. Therefore, we also investigated the dynamic of other protein markers involved in cognition and memory impairment such as metabotropic glutamate receptor 5 (mGluR5), ionotropic NMDA receptor (NMDAR2B), prion protein (PrPc) and amyloid precursor protein (APP), whose activity depends on membrane lipid organization. We observed a decline of these protein markers in LR fractions with the progression of aging and pathology. Overall, our findings demonstrate that lipid alterations in membranous compartments promoted by brain aging and PD-like injury may have an effect on α-syn aggregation and segregation in abnormal multimeric structures.